Sensitive double antibody sandwich ELISA for the quantification of phosvitin. Issue 5 (3rd September 2017) - Gujral, Naiyana; Yoo, Heejoo; Bamdad, Fatemeh; Suh, Joo-Won; Sunwoo, Hoon
ABSTRACT: An effective double antibody sandwich ELISA (DAS-ELISA) method based on monoclonal (mAb) and chicken egg yolk IgY antibodies was developed to determine phosvitin (PV) content in therapeutic and functional products. Leghorn laying hens were immunized with purified PV to produce anti-PV IgY antibody in the egg yolk. High anti-PV IgY titer obtained from the egg yolks collected during 4–10 weeks of the immunization period contained approximately 6.2% of specific anti-PV IgY in total IgY. The PV detection range of the DAS-ELISA and biotinylated DAS-ELISA was 16.8–90 and 7.5–40 ng/mL, respectively. However, biotinylated DAS-ELISA was the better method for PV quantification in terms of accuracy and sensitivity. This highly efficient PV detection method may recuperate the performance of the existing protein assay methods as well as facilitate future research on PV bioactivities and applications.